Sensitivity and specificity of waist circumference as a single screening tool for assessment of overweight and obesity - Karmakar, Anubrata; Garg, Shobhit; Dasgupta, Aparajita; Paul, Bobby; Maharana, Swanya P. (International Journal Of Community Medicine And Public Health, 2017)
Background: Generalised and central obesity are established risk factors for metabolic syndrome and cardiovascular diseases. Easy assessment of overweight or obesity is the need of the hour from public health perspective. Waist circumference (WC) can be a simple screening tool for identifying overweight individuals since measuring WC is simple, inexpensive, less time consuming, convenient for self-monitoring and needs no complicated calculation as BMI. Methods: A community based cross-sectional study was conducted in January-February 2017 among 338 adults, in a village of Singur Block, West Bengal. Height, weight and WC were measured for each subject. Receiver Operating Characteristic (ROC) curve analysis was used to estimate the cut-off values of WC. Results: The sensitivity and specificity of WC ≥90 centimeters for men for identifying overweight (BMI ≥25) were 78.8% and 75.6% respectively, whereas those of WC ≥80 cm for women were 80.3% and 44% respectively. ROC curve analysis revealed good diagnostic accuracy at 88.5 cm for WC cut-off for men (area under curve (AUC) 0.854, sensitivity 86.5%, specificity 67.6%) and fair accuracy (AUC 0.744, sensitivity 80.3%, specificity 44%) for WC cut-off for 80 cm for women. Conclusions: This study shows, WC can be used for screening of overweight individual infield practice as measuring tape is inexpensive and easy-to-carry compared to a weighing scale. More research may be done on larger sample size to establish an optimal WC cut-off value for Indian population.